Typical course of cystinuria leading to untypical complications in pregnancy: A case report and review of literature - Ivandic, Ema; Maric, Marjan; Elvedi-Gasparovic, Vesna; Fistrek Prlic, Margareta; Lamot, Lovro; Jelakovic, Bojan; Vukovic Brinar, Ivana (Frontiers in Medicine, 2023)
Cystinuria is a rare genetic disorder inherited by an autosomal recessive pattern which affects the transmembrane transporter for the base amino acid cystine. It has a general prevalence of 1 in 7000 with demographic variations. Patients with cystinuria have excessive urinary excretion of cystine, which can lead to the formation of stones. Up to 70% of patients will develop chronic kidney disease that can progress even to end-stage renal disease. Symptoms usually start in the first two decades of life with a typical presentation consisting of flank pain and renal colic, usually accompanied by urinary tract infection and deterioration of kidney function. Men are typically affected twice as often as women and have a more severe clinical course. Diagnosis is made by spectrophotometric analysis of the stones that are collected after spontaneous expulsion or medical intervention. Genetic testing is not mandatory but is recommended in uncertain cases or as a part of genetic counseling. Treatment consists of diet modification, alkalization of urine, and thiol-based therapies if other measures fail to prevent stone formation. In pregnancy, cystinuria with the formation of cystine stones represents a therapeutic challenge and requires a multidisciplinary approach consisting of an uro-nephrology team and a gynecologist. We present the case of a 34-year-old woman with cystinuria on whom the diagnosis was made by analysis of the expulsed stone. While her previous pregnancies were without complications, her third pregnancy was accompanied by frequent urinary tract infections, acute worsening of kidney function, and urological interventions during pregnancy due to the formation of new stones. Despite the complicated course, the pregnancy was successfully carried to term with the delivery of a healthy female child.